KESADARAN HUKUM DALAM MENAFKAHI ANAK PASCA PERCERAIAN PADA PUTUSAN PENGADILAN AGAMA SAMARINDA - Joy Agustian Irawan (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTLegal awareness is the awareness or values found in human beings about existing laws or expected laws that exist. legal awareness in fulfilling parental obligations in providing for a child after a divorce must be responsible for the costs of caring for and educating childrenThis research intends to know the legal awareness of parents in being responsible for all the costs of caring for and education for children after divorce and in general aims to find out the legal awareness and obligations of parents in fulfilling the rights of children after divorce in Samarinda's religious court ruling.The results of research in the Samarinda Religious Court, which occurred regarding children's living rights after divorce, all children from legal marriages come with their mothers and were the fulfillment of children's living rights is only fulfilling while there are not even full ones. In this case, many of which play a role after divorce is a mother who works to meet the needs of her children Apart that it should be the father who bears the living rights of the child that has been set by the Judge of the Samarinda Religious Court. Whereas in deciding the case, the judge's consideration is to see from a father's economic ability related to work and salary. Therefore, in deciding on cases involving the cost of living for children, the Samarinda Religious Court judges in considering and deciding based on the income of a father. Even though the Samarinda Religious Court's decision sentenced an ex-husband to fulfill his children's living rights after divorce, an ex-husband did not implement the decision. This is caused by several factors. Factors causing it are, First: economic factors, where an ex-husband on average does not have a steady income, even some who do not have a permanent job. Second: the mother factor is able to provide for her child, this is because a mother already has her own income. Third: communication factors, after divorce, many ex-husbands and ex-wives are no longer in communication. So it is very influential in terms of financing the livelihood of children.Keywords: Legal Awareness, Children's Livelihood